Recreation conflict and management options in the Vail Pass Winter Recreation Area, Colorado, USA - Miller, Aubrey D., author; Vaske, Jerry J., advisor; Squires, John R., committee member; Laituri, Melinda J., committee member (Colorado State University. Libraries, 2015)
This multi-part thesis focused on the underlying drivers of recreation conflict among winter recreationists in the Vail Pass Winter Recreation Area (VPWRA) in central Colorado. Data for the first manuscript were obtained from surveys collected in 2003 (n = 224, response rate = 93%) and again in 2014 (n = 242, response rate 89%) from randomly selected VPWRA non-motorized and motorized recreationists. A cluster analysis revealed significant changes in reported conflict over more than 10 years of recreation zoning at the VPWRA. Overall, the management system was effective at reducing, but not eliminating interpersonal conflict, while social values conflict increased over the period for non-motorized recreationists. Data for the second manuscript were collected from two sources: GPS units carried by recreationists in the VPWRA in 2010 and 2011 (n = 1,444,703, response rate = 90%), and survey data collected from non-motorized recreationists in the VPWRA in 2014 (n = 199, response rate 88% for on-site survey). A Geospatial analysis was performed to understand the extent of overlapping, or mixed non-motorized and motorized use occurring in the VPWRA. Then, a survey data analysis was conducted to test for differences in interpersonal conflict between non-motorized recreationists who traveled in mixed use areas, compared with those who did not travel in mixed use areas. Results suggest that interpersonal conflict is reported more often among non-motorized recreationists who traveled in areas of mixed use across five standard conflict variables. Themes from the analyses and management recommendations are discussed in the conclusion.